Professionalisierung von (angehenden) Lehrkräften im Bereich Sprachsensibler Fachunterricht an beruflichen Schulen (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2024)
Fachlehrkräfte beruflicher Schulen benötigen Kompetenzen zum sprachsensiblen Unterrichten, um in heterogenen Gruppen allen eine erfolgreiche Bildungsbeteiligung zu ermöglichen. Der Bei-trag stellt die Entwicklung neuer Lehrbausteine zur phasenübergreifenden Verankerung von Deutsch als Zweit-/Fremdsprache in die Hochschullehre der PH Freiburg vor und gibt Einblicke in die Herausforderungen und Chancen zweier Professionellen Lerngemeinschaften Sprachsen-sibler (Fach-)Unterricht. Subject teachers at vocational colleges should have competences in language-sensitive teaching, i.e. they should be able to conduct lessons in a way that enables all their students in heterogeneous groups to successfully participate in education. This article outlines the development of new study modules for anchoring German as a second/foreign language across all phases of teacher training at the PH Freiburg. Also, some insights concerning challenges and opportunities of setting up two Professional Learning Communities on language-sensitive (subject) teaching will be given.
Keywords: DaZ/DaF; Sprachsensibler Fachunterricht; Professionelle Lerngemeinschaft; berufliche Bildung; German as a Foreign/Second Language; language-sensitive teaching; Professional Learning Community; vocational education